The novel two-component system AmsSR governs alternative metabolic pathway usage in Acinetobacter baumannii - Casella, Leila G.; Torres, Nathanial J.; Tomlinson, Brooke R.; Shepherd, Mark; Shaw, Lindsey N. (Frontiers in Microbiology, 2023)
In this study we identify a novel two-component system in Acinetobacter baumannii (herein named AmsSR for regulator of alternative metabolic systems) only present in select gammaproteobacterial and betaproteobacterial species. Bioinformatic analysis revealed that the histidine kinase, AmsS, contains 14 predicted N-terminal transmembrane domains and harbors a hybrid histidine kinase arrangement in its C-terminus. Transcriptional analysis revealed the proton ionophore CCCP selectively induces PamsSR expression. Disruption of amsSR resulted in decreased intracellular pH and increased depolarization of cytoplasmic membranes. Transcriptome profiling revealed a major reordering of metabolic circuits upon amsR disruption, with energy generation pathways typically used by bacteria growing in limited oxygen being favored. Interestingly, we observed enhanced growth rates for mutant strains in the presence of glucose, which led to overproduction of pyruvate. To mitigate the toxic effects of carbon overflow, we noted acetate overproduction in amsSR-null strains, resulting from a hyperactive Pta-AckA pathway. Additionally, due to altered expression of key metabolic genes, amsSR mutants favor an incomplete TCA cycle, relying heavily on an overactive glyoxylate shunt. This metabolic reordering overproduces NADH, which is not oxidized by the ETC; components of which were significantly downregulated upon amsSR disruption. As a result, the mutants almost exclusively rely on substrate phosphorylation for ATP production, and consequently display reduced oxygen consumption in the presence of glucose. Collectively, our data suggests that disruption of amsSR affects the function of the aerobic respiratory chain, impacting the energy status of the cell, which in turn upregulates alternative metabolic and energy generation pathways.